2016
DOI: 10.1242/dev.133728
|View full text |Cite
|
Sign up to set email alerts
|

Integrin signalling regulates YAP/TAZ to control skin homeostasis

Abstract: The skin is a squamous epithelium that is continuously renewed by a population of basal layer stem/progenitor cells and can heal wounds. Here, we show that the transcription regulators YAP and TAZ localise to the nucleus in the basal layer of skin and are elevated upon wound healing. Skin-specific deletion of both YAP and TAZ in adult mice slows proliferation of basal layer cells, leads to hair loss and impairs regeneration after wounding. Contact with the basal extracellular matrix and consequent integrin-Src… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
337
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(361 citation statements)
references
References 109 publications
23
337
1
Order By: Relevance
“…9a,b). Consistent with YAP/TAZ being upregulated during epidermal development and wound healing, rather than in steady-state adult epidermis304142, we observed reduced IFE proliferation in neonatal (P5) but not adult WBP2 knockout mice (Fig. 4a,b and Supplementary Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…9a,b). Consistent with YAP/TAZ being upregulated during epidermal development and wound healing, rather than in steady-state adult epidermis304142, we observed reduced IFE proliferation in neonatal (P5) but not adult WBP2 knockout mice (Fig. 4a,b and Supplementary Fig.…”
Section: Resultssupporting
confidence: 78%
“…It is well documented that YAP and TAZ are required for normal epidermal development and hair growth in the mouse304142, and YAP and TAZ drive pro-tumorigenic signals in mouse and human cSCC3043. Nevertheless, there is ambiguity about YAP/TAZ function: YAP and TAZ are largely dispensible for homoeostasis of the IFE in adult mouse skin3042, and in cSCC both growth-promoting and growth-inhibiting functions have been documented4344.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, activation of ILK, which links F-actin to focal adhesions and is required for integrin-mediated force generation, sustains nuclear YAP accumulation in pulmonary arterial vascular smooth muscle cells to promote cell proliferation in pulmonary arterial hypertension, a disease characterized by increased deposition of extracellular matrix and vascular stiffness (Kudryashova et al, 2016). Consistent with this notion, regulation of Hippo activation by ILK (Serrano et al, 2013), Src-FAK (Kim and Gumbiner, 2015; Li et al, 2016), and beta1 integrins (Martin et al, 2016) has been observed in the context of epithelial-mesenchyme transition, cancer, as well as tissue homeostasis in the skin (Elbediwy et al, 2016). Although the physiological relevance of Hippo pathway regulation by integrins and their effectors needs to be confirmed in the context of fibrosis there is accumulating evidence supporting such a role.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 77%
“…Recently, the transcription factors YAP (Yes-associated protein) and TAZ (transcriptional coactivator with PDZ-binding motif, also known as WWTR1) have been suggested as key mediators in integrin-mediated mechano-transduction [37]. The nuclear localization of both factors seems to be regulated by contractile F-actin structures and maybe, by so far unidentified molecular effectors, depending on the cell type [37,38]. However, the detailed mechanisms and signalling hierarchy by which cytoskeletal tension regulates the translocation of YAP/TAZ await further evaluation.…”
Section: Integrinsmentioning
confidence: 99%